Studi kasus : Urolithiasis pada Kucing Milky di Klinik DRD Veteriner - Pangaribuan, Micco Joshua Apriano; Hermawan, Intan Permatasari; Sari, Dian Ayu Kartika (VITEK : Bidang Kedokteran Hewan, 2022)
Urolithiasis is a disorder of the urinary tract or urinary tract due to the presence of stones or calculi or crystals. These calculi can cause blockages to injury to the urinary tract. Specific clinical manifestations in this case are non-specific and highly variable, depending on the size, number, and location of calculi. Urolithiasis is generally followed by hematuria, dysuria, and stanguria. Milky cat came on 19 May 2022 at DRD Veterinary Veterinary Clinic with conditions of Hematuria, stranguria, and dysuria. When the temperature was measured using a thermometer, the temperature was 36.3 oC indicating the cat's temperature had decreased. examination to help diagnose milky cases by means of microscopic examination of urine, hematology and urinalysis, catheter insertion and cystotomy surgery.